The industrial player’s insight on current conditions of public playground for children with disabilities / Nor Suzila Lop ... [et al.] - Lop, Nor Suzila; Ab Wahab, Lilawati; Ismail, Kharizam; Hanid, Mahanim; Mohd Radzi, Nurul Asyikin (2022)
Over the last decade, children affairs risen to the top of government agendas at various times. Children today are the leader of tomorrow. Under public policy, every child is entitled to equal benefits against in regards to some issues. While equality demands everyone to be treated the same, children with disabilities (CWDs) frequently experience exclusion due to a disabling play environment. This exclusion is proven by previous research stating that CWDs engage in significantly less physical activity than their typically developing peers. Until recently, not much attention has been paid to the construction of playgrounds for children with disabilities. Cultivating appropriate inclusion in the play environment necessitates industry player awareness. On the other hand, the notion of children with disabilities playing is complex and multidisciplinary. Therefore, a focus group involving nine experts from industrial players that come from diverse backgrounds (i.e landscape architect, president of playground safety association of Malaysia, academician, and president of Persatuan Orang Cacat Penglihatan Islam Malaysia) was conducted to investigate the current conditions of public playground for disabled children. The results show that there are seven issues that have been identified during the focus group discussion on the current conditions of public playgrounds for CWDs in Malaysia in identifying the shortcomings that can be enhanced in designing playgrounds for CWDs. The issues are accessibility and mobility, safety factors, maintenance factors, compliance with provision / standard, suitability and usability of the play equipment, creating good environment, and low demand and supply of play equipment. Therefore, “loopholes” have been identified to facilitate the industrial players in designing right and ample space for CWDs playground in Malaysia.